Extracting Apis dorsata Binghamii Honey using Incision Technique - Rosmarlinasiah Rosmarlinasiah; Sitti Marwah; Meisanti Meisanti (International Journal of Agriculture System, 2014)
At the time of the flowering season arrives, honey bee colonies will actively fill the nest with honey, pollen and puppies. Along with the honey gatherers are also actively seeking to take the honey bee hive. Honeycomb (Apis dorsata Binghami) which has a hanging nest in trees was often taken by humans in an unproductive ways causing many young bees and hive contents besides honey, often wasted for the next harvest. The purpose of this study was to determine the slicing method honeycomb Apis dorsata Binghami in nature, which can speed up the next process in honey harvesting cycle. The sample consisted of eight observations of bee hive of Apis dorsata Binghami with four treatments and two replicates. Treatment P1 was slicing across the honeycomb, whereas nP2 treatment was the slicing/take part contains the honey hive, and treatment P3 used slicing whole beehive and later taped the sliced nest. P4 treatment had the honey extracted from the honey productive parts and then taped back the ex- slices from the middle of the nest. The results showed that the fastest time of bee colonies Apis dorsata Binghami back to the original nest is P4 treatment for it only took 0.000439 days while P2 took 0.000590 days. On the other hand P1 and P3 treatments took more than 80 days. Extracting just the honey from its nest will accelerate the bee colony reoccupation of their nest, compared with the whole slicing of the beehive. The faster the bee colony occupied the nest will result in quicker repair activities of the hive. The honey will be filled much faster for the next harvest revisits.